Parents Perceptions on School Readiness: Descriptive Study - Meria Susanti; Izzanil Hidayati; Nila Anggreiny; Yantri Maputra (GoAcademica Research & Publishing, 2023)
The purpose of this study is to explore the parents’ perceptions on Children’s School Readiness. The open-ended question was administered to 116 parents in Padang, Padang Panjang, Bukittinggi, and Sawahlunto, West Sumatera. Content analyses were used to categorize all the response from participants. Overall this study found that 84% participants’ think that school readiness are very important for children to enter elementary school, 15% said that it’s important, and 1% quite important. Most of the reasons are because school readiness helps children to be success in elementary school. Looking more closely about their perception on school readiness, participants think that school readiness is related to cognitive ability (27%), social skill (17%), emotional competence (14%), sufficient age (11%), physical development (11%). Another response is related to financial readiness and motivation. This finding indicated that many parents considered that cognitive ability such reading skill as one of significant factor for children to enter elementary school.